Assessment of Teacher Performance in SMK Informatika Bina Generasi using Electronic-Based Rating Scale and Weighted Product Methods to Determine the Best Teacher Performance - Syahrizal Dwi Putra; Rohmat Indra Borman; Gina Hapsari Arifin (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Teacher performance assessment is an assessment carried out on the main task activities as a teacher. The aim is to assess the performance of teachers in applying all competencies in the learning process, guidance to educational units and as a basis for planning continuous professional development for teachers. At SMK Informatika Bina Generasi, performance assessments were carried out on several teachers with the process of processing teacher performance appraisal data still semi-structured so it took time, tended to input data repeatedly and errors in data input, inefficient data storage resulted in a longer data search process. and the ongoing assessment has not supported decision-making on teacher performance assessments so that the school has difficulty determining achievement and evaluating teacher performance as a whole. The research method used is a qualitative research method by conducting literature studies, reviewing documents and interviews in determining teacher performance assessment instruments. The results obtained are a teacher performance appraisal system with an electronic-based rating scale method to assist schools and assessors in assessing teacher performance and obtaining teacher performance appraisal information more quickly, effectively and efficiently. In addition, this electronic-based teacher performance appraisal system is also equipped with the ability to rank all teacher performance using the weighted product method so that the best teacher performance is obtained.